Supervisi dalam Pendidikan Islam: Menyempurnakan Proses Pembelajaran Menuju Kualitas Pendidikan yang Unggul - Yulianto, Edi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This article aims to compare classical supervision with modern supervision. The research method used is content analysis by collecting data from scientific articles, books, and other sources. The findings of this paper are as follows: Supervision is carried out for no other reason than to foster educational actors in an organization to improve the quality of learning. In the ancient, ent sense, supervision,n is the inspection and examination process. With this ancient understanding, the supervisor becomes afraid, thus making himself not open to the problems that are afflicting him. In the current era, supervision comes in a humanist form, namely as a process of coaching, directing, assisting, serving, and providing assistance, and carried out on an ongoing basis with a directed and systematic program for teachers in improving their competencies. It is necessary to reflect on several things that are the basis of supervision in the world of education so that the purpose and principle of supervision will be realized in the world of education.